Exploring student engagement in fully flipped classroom pedagogy: Case of an Australian business undergraduate degree. Issue 2 (17th February 2022) - Fang, Jim; Vong, John; Fang, Jeff
Abstract: This paper aims to provide clear and appropriate evidence of factors that trigger student engagement of flipped classroom (FC) learning in higher education (HE), based on an example of a fully flipped business undergraduate degree program in Australia. Qualitative data from the Student Evaluation of Teaching and Units (SETU) of 142 first-year business students over seven consecutive trimesters (2017–2019) were gathered and analyzed using thematic analysis. The findings provide a nuanced understanding on triggers of student engagement in relation to self-efficacy, emotion, well-being and belonging. The findings may guide educators in full adoption of FC in other undergraduate courses.